Strengthening rural food security and community welfare through ICLS 5.0: A socio-biological approach to circular agriculture - Fawwaza, Kaylila Dalta; Rasyad, Muhammad Emirsyah; Putra, Moh Fatichul Yaqin Rizqi Mahesa (Journal of Earth Kingdom, 2026)
Background: Nutritional disparities remain a major challenge in Indonesia’s human resource development, as the prevalence of stunting and wasting continues to vary widely across regions despite measurable national progress. These inequalities highlight the need for integrated and sustainable agricultural innovations that improve both food quality and availability while maintaining ecological balance. This study aims to analyze the potential of the Integrated Crop–Livestock System (ICLS) 5.0 as an innovation that strengthens food security and enhances nutritional value through sustainable resource management. Method: A quantitative descriptive approach based on a comprehensive literature review was conducted using secondary data from scientific journals and national databases. The ICLS 5.0 framework emphasizes circular resource use, converting agricultural residues such as rice straw, corn stalks, and dry leaves into fermented forage, while livestock manure is processed into organic fertilizer through bioactivation and composting. Data were analyzed to assess improvements in productivity, soil fertility, and resource efficiency. Finding: Implementation of the ICLS 5.0 model can increase agricultural and livestock productivity by 30–40%, enhance soil carbon and nitrogen content, and reduce production costs by 30–50% through the substitution of chemical fertilizers and industrial feed. The system also reduces greenhouse gas emissions and improves food self-sufficiency in rural areas by promoting local feed and fertilizer production. Conclusion: The ICLS 5.0 approach provides a low-cost, scalable, and knowledge-based innovation that aligns with national efforts to strengthen food and nutrition security. By integrating crops and livestock within a circular economy framework, this model supports sustainable agricultural intensification and contributes directly to achieving Sustainable Development Goals (SDG 2 Zero Hunger, SDG 12 Responsible Consumption and Production, and SDG 13 Climate Action), while enhancing the resilience and welfare of rural farming communities. Novelty/Originality of this article: This innovation introduces an adaptive crop–livestock integration model suitable for various land scales, complemented by a localized ICLS framework. It also provides simple technical guidelines for converting organic waste into fertilizer, feed, or energy, along with the development of micro-scale circular economy systems for farmer and livestock groups.